2022
DOI: 10.3389/fpsyg.2022.825370
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Cardiac Interoception on the Self-Prioritization Effect

Abstract: Self-relevant information is processed faster and more accurately than non-self-relevant information. Such a bias is developed even for newly associated information with the self, which is also known as the self-prioritization effect (SPE). Interoception, which refers to the overall processing of information from within the body, is crucial for self-relevant processing; however, its role in SPE remains unexplored. In this study, we investigated the relationship between the magnitude of SPE and interoceptive ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 57 publications
(104 reference statements)
0
2
0
Order By: Relevance
“…Research on HBI has demonstrated that the cardiac cycle modulates perception (Barrett & Simons, 2015;Schulz et al, 2009), cognition (Garfinkel et al, 2014;Honda & Nakao, 2022), affective processing Gray et al, 2012), and action (Al et al, 2023). This evidence has been particularly relevant for psychiatric research, where mental .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Research on HBI has demonstrated that the cardiac cycle modulates perception (Barrett & Simons, 2015;Schulz et al, 2009), cognition (Garfinkel et al, 2014;Honda & Nakao, 2022), affective processing Gray et al, 2012), and action (Al et al, 2023). This evidence has been particularly relevant for psychiatric research, where mental .…”
Section: Introductionmentioning
confidence: 97%
“…Research on HBI has demonstrated that the cardiac cycle modulates perception (Barrett & Simons, 2015; Schulz et al, 2009), cognition (Garfinkel et al, 2014; Honda & Nakao, 2022), affective processing (Critchley & Garfinkel, 2017; Gray et al, 2012), and action (Al et al, 2023). This evidence has been particularly relevant for psychiatric research, where mental health conditions are associated with imbalances in brain-body interaction (Nord & Garfinkel, 2022; Khalsa et al, 2018; Khoury, Lutz, & Schuman-Olivier, 2018).…”
Section: Introductionmentioning
confidence: 99%